2021
DOI: 10.1108/ilt-07-2021-0252
|View full text |Cite
|
Sign up to set email alerts
|

Study on the influence of radial stiffness on the nonlinear vibration of brake system

Abstract: Purpose A dynamic model of the brake system considering the tangential and radial motion of the pad, and the torsion and wobbling motion of the disk is established in this paper. The influence of radial stiffness on the brake system is investigated under different tribological conditions. This paper aims to prove that sufficient radial stiffness is indispensable in the design of the brake system with good tribological performance. Design/methodology/approach By using the lumped mass method, a dynamic model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The friction model is required to simulate a continuous friction coefficient curve. Hereby, this paper adopts the Stribeck-type friction model (Yan et al , 2021) to predict frictional force at different friction velocities. Notably, this model avoids divergence when v r approaches 0, thus enhancing the computational efficiency: …”
Section: Model Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The friction model is required to simulate a continuous friction coefficient curve. Hereby, this paper adopts the Stribeck-type friction model (Yan et al , 2021) to predict frictional force at different friction velocities. Notably, this model avoids divergence when v r approaches 0, thus enhancing the computational efficiency: …”
Section: Model Introductionmentioning
confidence: 99%
“…As speed increases, the motion of the brake pad transitions from a single-period vibration to period-doubling bifurcation, entering a chaotic state and eventually devolving back into a single-period vibration (Wei et al , 2019). Yan et al (2021) established a brake system dynamics model that considered the tangential and radial movement of the brake pads and the torsional and swaying motion of the disc. They explored the impact of radial stiffness on the brake system under different friction parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the brake vibration was aggravated by the increase in the braking load and speed. Yan et al [19] studied the effect of radial stiffness on the vibration stability of a disc brake system under different friction conditions. Wang et al [20] established a rigid-flexible vehicle dynamics model and a finite element model of the braking system.…”
Section: Introductionmentioning
confidence: 99%